296 TO EVALUATE THE EFFECT OF ANGIOTENSIN-CONVERTING INHIBITORS ON HEMATOCRIT IN MODERATE TO SEVERE CHRONIC OBSTRUCTIVE PULMONARY DISEASE. (1st January 2005) - Mankan, N.; Joseph, M.; Razaq, M.; Kanagarajan, K.; Maini, A.
Abstract : Purpose of Study: Angiotensin-converting enzyme inhibitors (ACEI) are the drugs of choice for post renal transplant polycythemia (PTP). The etiology of PTP and the mechanism of action of ACEI in these patients are unclear. The most widely accepted mechanism of action includes reduction in erythropoietin synthesis and reduction in insulin-like growth factor 1. Whereas the medical literature is replete with data confirming activity of ACEI in PTP, it is scant and largely confined to case reports in the case of polycythemia due to the other causes. We studied a cohort of chronic obstructive pulmonary disease (COPD) patients who had pulmonary function tests done from April to September 2003. All patients with moderate (35-50%) to severe (< 35%) forced expiratory volume 1 were included in the analysis. The patients were divided into two subgroups depending upon whether or not they were receiving ACEI for any indication. The subgroup on ACEI should have been on the drug for a minimum of 4 months to be included in the analysis. Hematocrit trends were noted and compared in both the groups over and average period of 15 months of drug intake retrospectively. In the subgroup on the drug, hematocrit levels before and after starting ACEI was also compared. Analysis: Conclusion: ACEI may have a possible role in reducing the hematocrit in secondary polycythemia of other etiologies such as COPD. This may utilize the same mechanistic pathways as in PTP or different. Although our uncontrolled retrospective analysis of a relatively small number of patients could have suffered from several biases, the reduction in hematocrit in patients on ACEI is significant enough to pursue this hypothesis further and find clinical utility for this interesting phenomenon. ACEI are a very desirable adjunct to the currently available agents used for polycythemia vera. Conversely, a small fall in hematocrit may be observed in patients who are on ACEI for other indications like hypertension or CHF.